2003
DOI: 10.1007/s00223-002-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Potentiates the Combined Effects of Transforming Growth Factor-β and Tumor Necrosis Factor-α on Adult Human Osteoblast-like Cell Prostaglandin E2 Biosynthesis

Abstract: Reports that estrogen treatment modulates arachidonic acid metabolism by bone and bone cells are found in the literature. However, conflicting indications of the relationship that exists between estrogen and arachidonic acid metabolism emerge from the analysis of those reports. The present studies were undertaken to determine if estrogen effected the production of prostaglandins (PG) in human osteoblast-like (hOB) cell cultures derived from adults, under basal or cytokine-stimulated conditions. A 48-hour estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Previous work reported from this laboratory (Xu et al, 1997) demonstrated that TGFβ and TNFα can independently elevate the levels of COX-2 mRNA resulting in increased formation of PGE 2 . When both cytokines were added to specimens concurrently, the independent stimulation of hOB cell COX-2 mRNA levels, protein levels, and prostaglandin biosynthesis was further elevated (Xu et al, 1997;Secreto et al, 2003). Some researchers have reported that TGFβ can stimulate COX-2 mRNA expression in MC3T3-E1 cells (Pilbeam et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work reported from this laboratory (Xu et al, 1997) demonstrated that TGFβ and TNFα can independently elevate the levels of COX-2 mRNA resulting in increased formation of PGE 2 . When both cytokines were added to specimens concurrently, the independent stimulation of hOB cell COX-2 mRNA levels, protein levels, and prostaglandin biosynthesis was further elevated (Xu et al, 1997;Secreto et al, 2003). Some researchers have reported that TGFβ can stimulate COX-2 mRNA expression in MC3T3-E1 cells (Pilbeam et al, 1997).…”
Section: Discussionmentioning
confidence: 99%